Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data. (12th July 2020) - Davis, Genevieve E.; Baumgartner, Mark F.; Corkeron, Peter J.; Bell, Joel; Berchok, Catherine; Bonnell, Julianne M.; Bort Thornton, Jacqueline; Brault, Solange; Buchanan, Gary A.; Cholewiak, Danielle M.; Clark, Christopher W.; Delarue, Julien; et al.
Abstract: Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35, 033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution. Abstract : Limited information exists on the distribution and movement patterns for most baleen whale species in the western North Atlantic Ocean. Previously, we conducted a broad‐scale passive acoustic monitoring study to analyze North Atlantic right whale seasonal distribution and shifts therein, based on identified changes in occurrence patterns starting in 2010. This study uses similar acoustic datasets and protocols to understand the seasonal distribution of humpback, sei, fin, and blue whales within the western North Atlantic, and to determine whether any of these species exhibited similar shifts in distribution patterns across time.